A Qualitative Descriptive Study of Risk Reduction for Coronary Disease among the Hong Kong Chinese. Issue 4 (30th September 2013) - Chan, Choi Wan; Lopez, Violeta
Abstract Objectives Achieving optimal control and reduction in coronary heart disease (CHD) risks in Hong Kong (HK) remains significant and requires exploring. This article addresses the ability to reduce CHD risks among the HK Chinese. Design and Sample Through secondary analysis, a qualitative descriptive design using focus group interviews and content analysis were adopted. Older and younger adults were invited for the study. Measures An interview schedule was used to guide discussions during focus group interviews. Results Four categories emerged from the data: planning of health actions, control of risk‐reducing behavior, perceived opportunities for understanding CHD, and chest pain appraisal. Conclusions Local culture and population needs play a central role in disease perception and prevention. The findings are essential to target strategies for initiating health acts for younger adults and establish public education resources that underscore understanding of CHD risk, symptom recognition, and disease management, particularly among those middle‐aged and older people at high risk and with the diseased populations.